Messa a punto di un metodo per l’individuazione di β-1,3- glucanasi e chitinasi attraverso Native PAGE su estratti di piante di Prunus avium L. inoculate con Phytophthora spp. - De Rogatis, Anna; Guerri, Serena; Santini, Alberto; Ghelardini, Luisa (Annals of Silvicultural Research, 2026)
Tecnique to detect on ß-1,3- glucanase and chitinasi by native PAGE, in Prunus avium (L.)clones inoculated with Phytophthora spp. ß-1,3-glucanase and chitinase activities have been detected by native PAGE (poliacrylamide gel electrophoresis) on leaf extracts of wild cherry (P. avium) inoculated with different species of Phytophthora spp.. These pathogens are aggressive in wild cherry and they can cause wiltings and death of the plant. These two PR (pathogen-related) proteins are normally produced by plants as first resistance strategy towards pathogens. The PR activities are involved in ifal cell wall degradation and growth. Usually, the techniques to detect them are based on colorimetric assay performed with the total protein extracts or in the poliacrylamide gels, through expensive procedures. In this work a direct colorimetric detection on a Carboximetil (cm)-Curdlan RBB (Remazol Brilliant Blu) and Glycol Chitosan substrate, is used to reveal ß-1,3-glucanase and chitinasi respectively. This protocol resulted to be very sensible in detecting the two proteins, very simply, reliable and cheap.